2021
DOI: 10.3390/jpm11070617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C9 Genetic Polymorphisms on the Pharmacokinetics of Losartan and Its Active Metabolite E-3174: A Systematic Review and Meta-Analysis

Abstract: This study aimed to investigate the influence of CYP2C9 genetic polymorphisms on the pharmacokinetics of losartan and its active metabolite, E-3174, through a systematic review and meta-analysis. Eight studies published before March 2021 were included in this study. We used PubMed, the Cochrane Library, EMBASE, and Web of Science, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The data analysis was conducted through Review Manager (RevMan), version 5.3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…For example, losartan is biotransformed into its active metabolite, EXP-3174, mediated by the metabolizing enzyme, CYP2C9 . A relationship between CYP2C9 polymorphisms and the pharmacokinetics of ARBs have also been observed, although the clinical impact in terms of BP was modest ( 20 ). It has been shown that AGTR1 mediates the function of ARBs by association with G proteins that activate a phosphatidylinositol-calcium second messenger system ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, losartan is biotransformed into its active metabolite, EXP-3174, mediated by the metabolizing enzyme, CYP2C9 . A relationship between CYP2C9 polymorphisms and the pharmacokinetics of ARBs have also been observed, although the clinical impact in terms of BP was modest ( 20 ). It has been shown that AGTR1 mediates the function of ARBs by association with G proteins that activate a phosphatidylinositol-calcium second messenger system ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the metabolism of β blockers, anti-hypersensitive drugs, anti-arrhythmic drugs, and anti-depressants will not stop by AGP 2 as it does not inhibit CYP2D6 (Taylor et al 2020). AGP 2 also does not inhibit CYP2C9 which results in the metabolism of anti-clotting agents, anti-hypersensitive, anti-hypertensive, management of Type II Diabetes and Nonsteroidal Anti-Inflammatory (NSAIDs) (Park et al 2021). The CYP3A4 was not inhibited by AGP 2, which caused the oxidation of fatty acids, steroids, xenobiotics, and hormone synthesis (Samuels and Sevrioukova 2021).…”
Section: Adme Prediction Analysismentioning
confidence: 99%
“…They can selectively block the binding of angiotensin II in vascular smooth muscle and adrenal gland to its receptor subtype AT1, thus blocking the vasoconstriction and aldosterone secretion. However, ARBs are affected by drug metabolism enzyme gene polymorphism, which leads to individual differences in their antihypertensive efficacy [15]. There are few literature reports on whether the antihypertensive effect of ARBs is affected by intestinal flora.…”
Section: Introductionmentioning
confidence: 99%